2019
DOI: 10.1186/s12935-019-0941-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 promotes non-small cell lung cancer cells growth by regulating fatty acid metabolism

Abstract: Background Lung cancer is one of the most common malignant tumors worldwide. CD36 is a receptor for fatty acids and plays an important role in regulating fatty acid metabolism, which is closely related to tumorigenesis and development. The regulation of miR-21 and its role in tumorigenesis have been extensively studied in recent years. However, the relationship between miR-21 and CD36 regulated fatty acid metabolism in human non-small cell lung cancer remains unknown. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
(38 reference statements)
3
33
0
1
Order By: Relevance
“…Lipids which mainly include fatty acids and cholesterol are vital sources of energy metabolism in the human body [33]. Studies suggested that to meet the needs of biosynthesis during high levels of proliferation, the reprogramming of fatty acid (FA) metabolism becomes essential in cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Lipids which mainly include fatty acids and cholesterol are vital sources of energy metabolism in the human body [33]. Studies suggested that to meet the needs of biosynthesis during high levels of proliferation, the reprogramming of fatty acid (FA) metabolism becomes essential in cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…13 Another study reported that SNHG9 was downregulated in prostate cancer and predicted the survival of patients. 15 Therefore, SNHG9 may exhibit different expression patterns and play different roles in different types of malignancy. In our study, we found that SNHG9 was downregulated in NSCLC and its suppressive roles in NSCLC cell proliferation, which suggests that lncRNA SNHG9 may participate in the progression of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] It has been revealed that the upregulation of miR-21 promoted cell migration and cell growth in human non-small cell lung cancer cells through CD36 mediated fatty acid metabolism. 15 In addition, it was reported that the expression levels of miR-21 were elevated in NSCLC, and the expression of miR-21 was inversely correlated with overall survival of NSCLC patients, which indicated that miR-21 promoted the development of NSCLC. 19 In our study, we analyzed the TCGA dataset and observed downregulation of SNHG9 and its inverse correlation with miR-21 as well as its inhibitory roles in the regulation of the proliferation of non-small cell lung cancer (NSCLC) cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocyte-specific knockout of miR-21 in mice improved HFD-induced steatosis through upregulation of multiple miR-21-targeted pathways governing lipid metabolism [145]. In lung cancer cells, inhibition of miR-21 was shown to restrain FA uptake by down-regulating CD36 protein expression [146].…”
Section: Mirnas Involved In Lipid Metabolism Of Nalfdmentioning
confidence: 99%